Bamboo steamers and red flags : building discipline and collegiality among China's traditional rural midwives in the 1950s - Fang Xiaoping (2020)
This paper explores how the new Communist government developed a political consciousness of discipline and collegiality among traditional rural midwives in Chinese villages during the 1950s. It argues that selected traditional rural midwives were taught to observe discipline by attending meetings and studying, and to develop collegiality with peers through criticism and self-criticism of their birth attendance techniques and personal characters in short training courses from 1951 onwards. A legitimized midwife identity gradually formed in rural communities, but with it came conflicts and rivalry. By keeping these midwives under institutional surveillance and creating a dynamic and constant moulding process, the new government intended to foster professional and political discipline and collegiality within the group based on a normativized notion of selflessness performed within a changing series of indoctrination schemes that demonstrated continuity and complementarity and which I have described as common, preliminary, institutionalized, and dynamic schemes. This article examines how the state attempted to retrain marginalized and derided midwives with appropriate class backgrounds in order to incorporate them into the modern medical world, then still dominated by doctors and nurses with suspect class backgrounds. Ironically, in creating “socialist new people” to intervene in traditional rural birthing practices and introducing fee-for-service professionalism, the CCP accidentally created a degree of petit-capitalist thinking among women whose traditional mode of work may have been more selfless, thus complicating the process of indoctrinating selfless dedication.